2014
DOI: 10.1021/cm501899q
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Physical Properties of Ternary Phases around the Composition Cu5Sn2Se7 with Tetrahedral Coordination of Atoms

Abstract: A new monoclinic selenide Cu 5 Sn 2 Se 7 was synthesized, and its crystal and electronic structure as well as thermoelectric properties were studied. The crystal structure of Cu 5 Sn 2 Se 7 was determined by electron diffraction tomography and refined by full-profile techniques using synchrotron X-ray powder diffraction data: space group C2, a = 12.6509(3) Å, b = 5.6642(2) Å, c = 8.9319(4) Å, β = 98125(4)°, Z = 2; T = 295 K. Thermal analysis and high-temperature synchrotron X-ray diffraction indicated the deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
(59 reference statements)
4
28
1
Order By: Relevance
“…Interestingly, the intermediate cubic Cu 2–4 y Sn y Se alloyed structures that we found here could not be predicted by the bulk Cu 2 Se–SnSe 2 phase diagram, 31 and only in a recent work by Fan et al was a stable Cu 5 Sn 2 Se 7 compound, that is, with Cu 0.71 Sn 0.29 Se stoichiometry, reported for the first time. 39 On the other hand, the replacement of Cu + with Sn 4+ cations could not go beyond the Cu 2 SnSe 3 stoichiometry. Such experimental evidence can be easily rationalized by looking at the end, stable structure that would result from a complete replacement of Cu + with Sn 4+ cations, that is, trigonal SnSe 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the intermediate cubic Cu 2–4 y Sn y Se alloyed structures that we found here could not be predicted by the bulk Cu 2 Se–SnSe 2 phase diagram, 31 and only in a recent work by Fan et al was a stable Cu 5 Sn 2 Se 7 compound, that is, with Cu 0.71 Sn 0.29 Se stoichiometry, reported for the first time. 39 On the other hand, the replacement of Cu + with Sn 4+ cations could not go beyond the Cu 2 SnSe 3 stoichiometry. Such experimental evidence can be easily rationalized by looking at the end, stable structure that would result from a complete replacement of Cu + with Sn 4+ cations, that is, trigonal SnSe 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We discovered an ordered phase Cu5Sn2S7 crystallizing with a monoclinic structure described in the space group 𝐶𝐶2. This phase is isotypic to both Cu4NiSi2S7, 24 and to the homologous selenide Cu5Sn2Se7, 25 and can be obtained as a pure phase for x = 0.15. Despite the close compositions and common structural sphalerite framework, the new member of the Cu-Sn-S family is immiscible.…”
Section: Introductionmentioning
confidence: 97%
“…Among all the Cu-based TE materials, Cu 2 Se has received great attention recently, as it has good thermoelectric performance. To date, the electronic structures and thermal conductivity of Cu 2 Se have been modified by doping using Al, Sn, Sb, Ag, and Li in the Cu sites [8][9][10][11][12] , and Te, S, I, and Br in the Se sites. [13][14][15][16] Recently, it has been reported that various types of carbon incorporated Cu 2 Se composites exhibited high zT of ~ 1.8-2.4 at 850 K [17][18][19] using a melt fabrication process above the melting point of Cu 2 Se.…”
Section: Introductionmentioning
confidence: 99%